Mousse and murder - Logan, Elizabeth, 1937- (Logan, Elizabeth, 1937- Alaskan diner mystery., 2020)
A young chef might bite off more than she can chew when she returns to her Alaskan hometown to take over her parents' diner in this charming first installment in a new cozy mystery series set in an Alaskan tourist town.